Development of application to automatically calculate mean amplitude of glycaemic excursions using intermittently scanned continuous glucose monitoring data - Kitae, Aya; Kimura, Tetsuya; Munekawa, Chihiro; Hosomi, Yukako; Osaka, Takafumi; Kitagawa, Noriyuki; Ushigome, Emi; Yamazaki, Masahiro; Hamaguchi, Masahide; Fukui, Michiaki (Diabetes, Obesity and Metabolism, 2021)
Aim We aimed to develop an application to calculate mean amplitude of glycaemic excursions (MAGE) automatically and to evaluate its accuracy. Materials and Methods We named the application intermittently scanned continuous glucose monitoring (isCGM) calculator KAMOGAWA (Kyoto Auto MAGE Of Glucose cAlcutator With isCGM Application). The isCGM data from 20 patients, 10 with and 10 without diabetes, were used to compare manually calculated MAGE values with those calculated using KAMOGAWA. The rate of agreement for the MAGE values was calculated. Results Comparing the MAGE values calculated manually with those calculated using KAMOGAWA, the total mean rate of agreement was 81.6%. Nonmatching values were checked and it was found that the inconsistencies were all attributable to errors in manual calculations. After correcting errors in the manual calculation, the MAGE values matched to one decimal place for all data in the manual and KAMOGAWA calculations. Conclusions KAMOGAWA can help diabetologists use MAGE in clinical practice, which could contribute to improving glycaemic control in patients who use isCGM.